Adult Ewing Sarcoma: Survival and Local Control Outcomes in 102 Patients with Localized Disease. (11th June 2013) - Ahmed, Safia K.; Robinson, Steven I.; Okuno, Scott H.; Rose, Peter S.; Laack, Nadia N. Issa
Abstract : Objectives . To assess the clinical features and local control (LC) outcomes in adult patients with localized Ewing Sarcoma (ES). Methods . The records of 102 ES patients with localized disease ≥18 years of age seen from 1977 to 2007 were reviewed. Factors relevant to prognosis, survival, and LC were analyzed. Results. The 5-year overall survival (OS) and event-free survival (EFS) were 60% and 52%, respectively, for the entire cohort. Treatment era (1977–1992 versus 1993–2007) remained an independent prognostic factor for OS on multivariate analysis, with improved outcomes observed in the 1993–2007 era (P = 0.02 ). The 5-year OS and EFS for the 1993–2007 era were 73% and 60%, respectively. Ifosfamide and etoposide based chemotherapy and surgery were more routinely used in the 1993–2007 era (P < 0.01 ). The 5-year local failure rate (LFR) was 14%, with a 5-year LFR of 18% for surgery, 33% for radiation, and 0% for combined surgery and radiation in the 1993–2007 era (P = 0.17 ). Conclusion . Modern survival outcomes for adults with localized ES are similar to multi-institutional results in children. This improvement over time is associated with treatment intensification with chemotherapy and increased use of surgery. Aggressive LC (combined surgery and radiation) may improve outcomes in poor prognosis patients.